Effect of Sintering Temperature on BPSCCO Superconductor with Addition of Al2O3 Using Wet Mixing Method - Aturroifah, Nuviya Illa Muthi; Wicaksono, Adi Tri; Hidayah, Ade Siyanti Nurul; Diantoro, Markus (Universitas Negeri Malang, 2023)
Superconductors are materials that can conduct electric current without resistance. The application of superconducting materials in the field of transportation is the super-fast train or Magnetic Levitation (MagLev). BPSCCO added with Al2O3 nanoparticles has been successfully synthesized using the wet mixing method. In this study, variations in the sintering temperature (840 and 880oC) were carried out using the wet mixing method. The performance of BPSCCO with the addition of Al2O3 was carried out by testing XRD, SEM, and I-V. Based on the results of XRD characterization, the volume fraction, impurity, and crystal size respectively were 57.49% (BPSCCO-840), 38.96% (BPSCCO-880); 42.5% (BPSCCO-840), 38.96% (BPSCCO-880) and 21.38 nm (BPSCCO-840); 28.84 nm (BPSCCO-880). Based on the results of the SEM test, the sample slabs are regular and have little free space. Based on the I-V test results, the BPSCCO-840 sample has the highest electrical conductivity of 2.4x104 S/m at a current of 0.6 mA and the BPSCCO-880 sample has a conductivity of 2.8x104 S/m at a current of 0.3 mA